PERBANDINGAN PERENCANAAN TEBAL PERKERASAN LENTUR DENGAN METODE ANALISA KOMPONEN BINA MARGA 1987 DAN MDPJ 2017 JALAN WISATA PENANGKARAN PENYU TALAO PAUAH PARIAMAN - Dediansyah Dediansyah; Helga Yermadona; Deddy Kurniawan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Roads as one of the transportation infrastructure that play an important role in people's lives in increasing economic activity in a place because it helps people to go or send goods faster to their destination. With the construction of this road, it is hoped that it will increase and accelerate the distribution of agricultural products, plantations and the basic needs of the surrounding community. Road pavement is a layer structure that is located above the subgrade, there is a layer of the top foundation and the bottom foundation which each layer consists of compacted aggregates which have a function to transmit stresses due to wheel loads. included in this study using the 1987 Bina Marga Component Analysis Method and the 2017 MDPJ Method. The location of this research is located in the Talao Pauh Pariaman turtle sanctuary. The results of the pavement layer analysis method of Bina Marga 1987 for new road pavements were obtained for the surface layer (D1) which was 10 cm, the upper foundation layer (D2) was 20 cm and the lower foundation layer (D3) was 11.5 cm. And the results of the 2017 MDPJ Pavement Layer Method for new road pavements are obtained for the surface layer which is 17 cm (D1), the top foundation layer (D2) is 19 cm and the lower foundation layer (D3) is 50 cm.Keywords: flexible pavement, MDPJ 2017, Talao Pauah Pariaman.